Discursos, hegemonia e agronegócio: tensão e luta de classes no contemporâneo - Scherma, Camila Caracelli (2010)
In this work we purpose a study of the relationships and discursive struggles that are established on material bases of society, the infrastructure, through the discourses that are produced about the economical activities linked to agribusiness. We are interested in understanding how the actions of the concrete base are prepared, justified and modified through discourses, through word, through signs. Thus, by the study of various discourses collected in the most varied spheres of human activity, of many different genres, we intend to build a comprehension of the tense ideological and discursive struggles that are waged in the materiality of the enunciations, according to divergent conceptions, values and positions related to agricultural and livestock activities on a large scale - agribusiness. That's if we consider that there are discourses that construct this economic activity as the key to the economic development of our country, and to sustain this position, struggle to maintain and strengthen the present order of things; and, by the other hand, there are conceptions that link all these efforts and investments to reinforce the historical Brazilian position as a supplier of raw materials to the international market. The discursive differences are ideological differences, which constitute a clash between stability and instability, a discursive struggle, which is an ideological struggle, since that ideological signs that constitute the discourses refract e reflect the same reality in different ways, since they are grounded on class interests.